Linguistic accuracy and authenticity of the content of the Russian version of the module of gastrointestinal symptoms of the PedsQL™ questionnaire for pediatric patients - Anna L. Arakelyan; Andrey N. Surkov; Aleksander A. Baranov; Leyla S. Namazova-Baranova; Valeri V. Gorev; Elena B. Moskvina; Tamara A. Skvorcova; Artem V. Nikitin; Vladislav V. Chernikov (Педиатрическая фармакология)
Background. Health Related Quality of Life (HRQL) is a person’s perception of the effect of a disease on physical, social and psychological functioning and wealth. Questionnaires that help assess the HRQL can give a concept of child’s state, identify arcane issues and they are of great importance for a full understanding of how the state of health affects the child. Universal HRQL tools allow to compare results with general parameters, indicators with specific symptoms better reflect clinically significant moments. The most widespread in the Russian Federation was the general PedsQLTM 4.0 questionnaire, widely used in practice to assess HRQL in children with various pathologies. Objective.The aim of the study is to describe the analysis of linguistic accuracy and authenticity of the content of the Russian version of the module of gastrointestinal symptoms of the PedsQLTM questionnaire, measuring HRQL, in children with gastrointestinal disorders (GIDs).Materials and methods. The establishment of linguistic accuracy and authenticity of the content was carried out according to international standards. The process included forward translation, scientific assessment and coordination, reverse translation, verification of the reverse translation and interviews with 17 children aged 5–18 years with symptoms of GIDs and 20 parents of children with symptoms of GIDs aged 2–18 years.Results. The Russian version of PedsQLTM module of gastrointestinal symptoms (report from children 5-18 years old, report from parents for children 2–18 years old) was developed without significant difficulties. Eight questions required discussion after the forward translation, one change was made after the reverse translation, and three changes were made after the study of the symptom’s module by patients and parents.Conclusion. A conceptually equivalent version of the of PedsQLTM module of gastrointestinal symptoms in Russian has been developed for children aged 2–18 years. It allows to improve the assessment of HRQL in children with GIDs in the Russian Federation. To assess authenticity and reliability of the Russian version of the module, it’s recommended to conduct further research using a larger sample